2022
DOI: 10.1088/1674-1056/ac4a74
|View full text |Cite
|
Sign up to set email alerts
|

Effect of void size and Mg contents on plastic deformation behaviors of Al–Mg alloy with pre-existing void: Molecular dynamics study

Abstract: The plastic deformation properties of cylindrical pre-void Aluminum-Magnesium (Al-Mg) alloy under uniaxial tension are explored using molecular dynamics simulations with embedded atom method (EAM) potential. The factors of Mg content, void size, and temperature are considered. The results show that the void fraction decreases with increasing Mg in the plastic deformation, and it is almost independent of Mg content when Mg is beyond 5%. Both Mg contents and stacking faults around the void affect the void growth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 50 publications
1
2
0
Order By: Relevance
“…Such perturbations in the lattice structure lead to a diminution in the alloy's stiffness. This pattern finds corroboration in the study by Wei et al [18], who documented a decline in the modulus of elasticity in Al-Mg alloys with heightened magnesium content, thereby validating the outcomes derived from the present study.…”
Section: Ml-based Analysis 421 Exploratory Data Analysissupporting
confidence: 92%
See 1 more Smart Citation
“…Such perturbations in the lattice structure lead to a diminution in the alloy's stiffness. This pattern finds corroboration in the study by Wei et al [18], who documented a decline in the modulus of elasticity in Al-Mg alloys with heightened magnesium content, thereby validating the outcomes derived from the present study.…”
Section: Ml-based Analysis 421 Exploratory Data Analysissupporting
confidence: 92%
“…Kumar and Das [15] delineated the mechanical properties of Al-Mg alloy across varying Mg concentrations employing the MD paradigm, noting a decrement in mechanical properties with elevated Mg content. Pogorelko and Mayer [16], Samiri et al [17], and Wei et al [18] further contributed to understanding the influence of various factors such as strain rate, temperature, and Mg content on the alloy's mechanical properties. Lee et al [19] and Chabba and Dafir [20] also provided valuable insights into the effects of magnesium content on the alloy's tensile and compressive properties.…”
Section: Introductionmentioning
confidence: 99%
“…Molecular dynamics (MD) simulation provides an alternative method to experiments, which plays an important role in understanding the deformation mechanism in metallic materials. [35][36][37][38] Actually, the mechanical properties of the crystalline/amorphous nanolaminates have been investigated in the past few years using MD simulation. [39][40][41][42] Tran and Fang [39] reported that the plastic deformation zones increase as the thickness of each layer decreases in crystalline/amorphous Cu/CuTa nanolaminates.…”
Section: Introductionmentioning
confidence: 99%